Ambiguous apparent motion in exchanging disks - Stuart Anstis; Nihan Alp (i-Perception)
A large and a small disk with radii R and r , side by side, exchange positions repetitively at 1.33 Hz. The motion is ambiguous. If r / R   < 0.8 then observers perceive a single large disk jumping back and forth across a small static disk. But if r / R   > 0.8, observers perceive two static disks that expand and contract in counter phase, with no motion across the gap between the disks. Observers respond to the movement of the centroid , which is greatest when r / R   < 0.8.